1992
DOI: 10.1007/bf00051653
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of alcohol, coffee, and tobacco, and gastric cancer in Spain

Abstract: A case-control study on gastric cancer was carried out between 1987 and 1989 in four regions of Spain. Three hundred and fifty-four cases of histologically confirmed adenocarcinoma were included (235 men and 119 women). For each case, a control was selected, matched by sex, age, and area of residence, from the same hospital as the case. No association was observed with smoking, nor with the consumption of coffee or tea. The usual consumption of alcohol was associated with gastric cancer in men (odds ratio = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Twenty-three studies 16,32,33,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58 remained for quantitative data synthesis ( Figure 1 and Table 2). There were 7 cohort studies, with follow-ups ranging from 4.3 to 15 years, and 16 case-control studies, 10 hospital-based, 5 populationbased, and one with no specified study base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies 16,32,33,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58 remained for quantitative data synthesis ( Figure 1 and Table 2). There were 7 cohort studies, with follow-ups ranging from 4.3 to 15 years, and 16 case-control studies, 10 hospital-based, 5 populationbased, and one with no specified study base.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al 42 Agudo et al 43 (F) Agudo et al 43 (M) Hoshiyama & Sasaba 33 Memik et al 16 Hansson et al 44 Inoue et al 45 Stensvold & Jacobsen 54 …”
Section: (M)mentioning
confidence: 99%
“…4,7,10,11,[40][41][42][43][44][45][46][47][48] While beer consumption was associated with a 1.7-fold to 1.8-fold increase in risk of total gastric cancer on noncardia gastric cancer in casecontrol studies in Uruguay, 4 the United States, 11 and Germany, 40 vodka was the only beverage related to an increased risk in casecontrol studies in Russia 10 and Poland. 41 Beer and hard liquor consumption was associated with a nonsignificant 1.3-fold to 2.1-fold elevated risk of gastric cancer in studies from Spain, 42 United States, 43 and China. 48 Wine consumption was positively associated with risk of gastric cancer in case-control studies in France, 44 Portugal, 45 Uruguay, 46 and Italy 47 but with a reduced risk in studies conducted in Sweden, 7 Germany, 40 and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk of stomach cancer among smokers has been observed in numerous case-control and cohort studies (10)(11)(12)(13)(14)(15)(16) and is consistent with our study too. However, studies from Europe have reported no association between stomach cancer and smoking (17)(18)(19)(20)(21)(22)(23). Smoking as a variable risk factor for stomach cancer has also been reported from India (24,25).…”
Section: Discussionmentioning
confidence: 99%